Side reactions and stability of pre-treated carbon felt electrodes for vanadium redox flow batteries: A DEMS study. (March 2020) - Eifert, L.; Jusys, Z.; Behm, R.J.; Zeis, R.
Abstract: The identification and quantification of the side reactions in all-vanadium redox flow batteries are crucial to maintain its performance and to develop optimized materials. We altered the chemical composition and structure of the carbon felt electrodes by thermal treatment, chemical, and electrochemical aging, and also storing thermally treated felts for an extended period, which represent several stages in its life. The treated felts were evaluated regarding their affinity to side reactions and electrochemical activity towards both relevant vanadium redox couples (V 2+ /V 3+ and V 4+ /V 5+ ). Differential electrochemical mass spectrometry was utilized to track the potential dependant formation of CO2 and O2 on the positive electrode side and of H2 on the negative electrode side. Storing thermally treated felts for an extended period under ambient conditions results in a slightly decreased electrochemical performance and an increased CO2 formation due to oxidation by atmospheric oxygen. The V 4+ /V 5+ redox reaction is hampered on electrochemically aged carbon felts, while they show an increased electrochemical activity towards the V 2+ /V 3+ redox reaction, thus allowing recycling of aged cathode felts as an anode felt and therefore extending the overall lifetime of the carbon felt electrode. Graphical abstract: Image 1